Sosialisasi Dan Pengembangan Strategi Digital Marketing Guna Modernisasi Pemasaran Pada Paguyuban UMKM Kalirungkut - Rahayu Musfirah; Uci Silvia Rahmah; Akmat Syaifudin; Arinal Haq; Eka Mas Tommy Airlangga (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Kalirungkut Village is an area that has various potentials. One of the superior potentials of the village located in Rungkut District, Surabaya is Micro, Small and Medium Enterprises (MSMEs). Many MSME actors have joined the Kalirungkut MSME Association. Association member products are dominated by food and beverages. In addition, there are several MSMEs selling crafts. On the other hand, running a business is not an easy thing. Many MSME actors are constrained, both internal and external constraints. Based on surveys and observations, the main problem faced by members of the Kalirungkut MSME Association is marketing which is still simple and traditional so that it affects the slow, even stagnant, development of MSMEs. Therefore, the East Java MBKM